PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS HOTS PADA MATERI SISTEM PERNAPASAN MANUSIA DI KELAS XI IPA SMA NEGERI 1 ONOLALU - Rofy Armin Harita (Universitas Nias Raya, 2026)
The lack of HOTS-based learning modules on the human respiratory system at SMA Negeri 1 Onolalu became the basis for this research. At SMA Negeri 1 Onolalu, the aim of this research is to create a learning module for material on the human respiratory system that is reliable, useful and efficient. This type of research uses the PLOMP (research and development) development model. Twenty class XI Science students at SMA Negeri 1 Onolalu participated in this research testing. To normalize items, three stages of testing were carried out, namely special legitimacy testing, common sense testing, and viability testing. Assessment questionnaires with Likert scales and evaluation test questions are instruments used to determine student learning outcomes. With a percentage of 90.4%, research shows that this HOTS-based learning module is useful and very valid. The students’ very practical score was 3.57, while the average teacher practicality score was 3.6. With a score of 91.3%, student learning motivation is classified as very high, and student learning outcomes are classified as adequate, with an average cognitive score of 88.65 compared to the score before using the module of 65.7. Researchers suggest that teachers can incorporate HOTS-based learning modules into the learning process because they can increase students’ interest and motivation to learn, and students can use the developed HOTS-based learning modules more positively. This HOTS-based learning module can be a useful research reference for future researchers.